ДИДАКТИЧНІ ЗАСАДИ НАВЧАННЯ РИТОРИКИ У ВИЩИХ НАВЧАЛЬНИХ ПЕДАГОГІЧНИХ ЗАКЛАДАХ (Педагогіка вищої та середньої школи, 2022)
In the article the basic approaches are defined and analyzed, the main didactic and specific principles which define modern sense of process of rhetoric training in the institute and provide its efficiency.